COURAGE AND STRENGTH OF ANCESTORS IS THE BASIS OF OUR PROSPEROUS DAYS - Burkhanov, Qutbiddin (Oriental Journal of Education, 2023)
Our current prosperous life is due to the bravery and fortitude shown by our ancestors in the Second World War. It is both a duty and a duty for us to pay tribute to the souls of our ancestors who died in the Second World War. Because, no doubt, no matter how many years and times pass, the value and importance of the victory achieved in this war will continue to increase. In this article, we talked about the courage shown by our ancestors.